1 year?

Answer:

**Answer:**

Steven ears $565 more in one year.

**Step-by-step explanation:**

Giving the following information:

Mark:

PV= $45,000

n= 1

i= 0.032

Steven:

PV= $45,000

n= 1

i= 0.045

**To calculate the Future Value of each investment, we need to use the following formula:**

**FV= PV*(1+i)^n**

**Mark:**

FV= 45,000*1.032= $46,440

**Steven:**

FV= 45,000*1.045= $47,025

Difference= 47,025 - 46,440= $565

Steven ears $565 more in one year.

Answer:
### Final answer:

### Explanation:

### Learn more about Compound Interest here:

After investing their inheritance for one year, Steven has $585 more than Mark due to the higher interest rate of his investment.

After one year, the amount of money Mark and Steven have can be calculated using the formula for compound interest, which is P(1 + r) to the power of n, where P is the principal amount, r is the annual interest rate, and n is the time in years. So, **Mark's future value** would be $45000(1 + 0.032) = $46440. In contrast, **Steven's future value** would be $45000(1 + 0.045) = $47025. Therefore, Steven has $47025 - $46440 = $585 more than Mark after 1 year.

#SPJ3

Disk requests come in to the disk driver for cylinders 10, 22, 20, 2, 40, 6, and 38, in that order. A seek takes 6 msec per cylinder. How much seek time is needed for (a) First-come, first served. (b) Closest cylinder next. (c) Elevator algorithm (initially moving upward). In all cases, the arm is initially at cylinder 20.

Jack buys a bag of 5 apples, eachequal in size. He eats of 1/2 of one apple. What fraction of the bag ofapples did he eat?

What is the volume of the cone below

Please help so urgent

G(x) = 2x − 1 h(x) = 1 − g(x) The functions g and h are defined above. What is the value of h(0)?

Jack buys a bag of 5 apples, eachequal in size. He eats of 1/2 of one apple. What fraction of the bag ofapples did he eat?

What is the volume of the cone below

Please help so urgent

G(x) = 2x − 1 h(x) = 1 − g(x) The functions g and h are defined above. What is the value of h(0)?

**Answer:**

**Step-by-step explanation:**

Start with:

Distribute by multiplying:

You're left with:

(2) (-3x) + (2) (3x) please mark me the brainliest

Show work

**Answer:**

Center: (3, - 4)

**Step-by-step explanation:**

We can start to solve this problem by converting this equation into standard form. In other words, by completing the square --- (1)

Subtract " 10 " from either side of the equation x² + y² - 6x + 8y + 10 = 0

x² + y² - 6x + 8y = - 10

Step 1: Complete the square for the expression " x² - 6x "

Using the quadratic equation ax² + bx + c we know that a = 1, b = - 6, c = 0. Assume that d = b / 2a. We have...

d = - 6 / 2(1) = - 6 / 2 = - 3

Now let's assume that e = c - (b²) / 4a...

e = 0 - (-6)² / 4(1) = 0 - 36 / 4 = 0 - 9 = 9 (Substitute values d and e)

(x - 3)² - 9

Step 2: Respectively we can complete the square for the remaining expression " y² + 8y "

Here a = 1, b = 8, c = 0

d = 8 / 2(1) = 8 / 2 = 4

e = 0 - (8)² / 4(1) = 0 - 64 / 4 = 0 - 16 = - 16 (Substitute values)

(y + 4)² - 16

This leaves us with the expression " (x - 3)² - 9 + (y + 4)² - 16 = - 10. " If we simplify this a bit further it leaves us with the following circle equation. Using this we can identify the center of the circle as well --- (2)

**As you can see our center here is (3, - 4)**

**Answer:**

165°

**Step-by-step explanation:**

**Find the interior angle measure by using the formula, ((n - 2) x 180°) / n**

**Plug in 24 as n:**

((n - 2) x 180°) / n

((24 - 2) x 180°) / 24

(22 x 180°) / 24

3960 / 24

**= 165**

So, the measure of each angle is **165°**

Answer:

163.6

Step-by-step explanation:

180•(22-2)=180•20 =3600

3600/22= 163.636363…

one way is to factor the expressions

(a)

(1.2 + (5.35 × ))

= (1.2 + 53.5)

= 54.7 × = 5.47 × × = 5.47 ×

(b)

((6.91 × ) + 2.4)

= (69.1 + 2.4)

= 71.5 × = 7.15 × × = 7.15 ×

(c)

((9.7 × ) + 8.3)

= (97 + 8.3)

= 105.3 × = 1.053 × × = 1.053 ×

(d)

((3.67 × ) - 1.6)

= (36.7 - 1.6)

= 35.1 × = 3.51 × × = 3.51 ×

(e)

((8.41 × ) - 7.9)

= (84.1 - 7.9 )

= 76.2 × = 7.62 × × = 7.62 ×

(f)

((1.33 × ) - 4.9 )

= (13.3 - 4.9) = 8.4 ×

a. 3,628,800

b. 1,814,400

c. 100

d. 0

the answer is A.. I HAD THE SAME QUESTIONN]

The correct answer is A

**Answer:**

135 times

**Step-by-step explanation:**

**Answer:**

135

**Step-by-step explanation:**